Multi-dimensional superposition: Rural collaborative governance in Liushe Village, Suzhou City - Zhang, Qingyuan; Ye, Chao; Duan, Jinjun (Journal of rural studies, 2022)
Rural governance has become a hot topic alongside rapid urbanization, especially in several Global South countries. Under China's new-type urbanization, rural and suburban space in the Yangtze River Delta has entered the metropolitan system. The rural-urban boundary has been blurred, reflecting the characteristics of planetary urbanization. Rural governance in the metropolitan fringe areas exhibits characteristics different from that in the traditional rural areas. Taking Liushe Village of Suzhou as a typical case, this study linked planetary urbanization to collaborative governance theory and constructed a multi-dimensional conceptual framework to explore the process, characteristics, and mechanism of its rural governance based on qualitative research methods. Liushe has undergone three stages under rapid urbanization: traditional agriculture, ecological conservation, and culture-tourism integration, which have led to the continuous transformation of the rural governance mode. Local governments, creative entrepreneurs, and the village collective are the three key subjects in formulating collective actions. The collaborative governance of Liushe reflects the multi-dimensional superposition of institutional design, social capital, and collective attributes. The case study provides a reference for exploring China's new rural governance mode. The rural spatial reconstruction of Liushe Village partly supports the view of planetary urbanization, whereas its multiple logics under unique institutional conditions expand the research framework of collaborative governance. •A multi-dimensional framework for rural collaborative governance is put forward based on planetary urbanization theory and collaborative governance theory.•The effects of China's rural-urban relations and key actors including local governments, creative entrepreneurs, village collectives on rural spatial governance are analyzed.•The effective complementation of urban and rural spatial functions and flexible entry and exit mechanism of social capital are the key to the success of rural governance in East China's metropolitan fringe.•Combination of top-down support or direction led by governments and bottom-up self-governing led by village collective is a feasible path for efficient rural spatial governance.